2018
DOI: 10.1007/s11605-018-3702-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Drains Contribute to Pancreatic Fistulae? Analysis of over 5000 Pancreatectomy Patients

Abstract: Despite randomized controlled clinical trial data supporting no drain placement, drains are currently placed in the vast majority (87%) of pancreatectomy patients from > 100 institutions in the USA, particularly those with soft glands, small ducts, and perioperative blood transfusions. When these factors are controlled for, drain placement remains independently associated with fistulae after both distal and proximal pancreatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Actually, this patient had a primary pancreatic head carcinoma and a swelling and brittle pancreatic body, which might be one of the major reasons for postoperative pancreatic fistula. 40 Although the anastomotic tissue sample was not available in the current study, our previous animal studies have demonstrated that there was always a smoother anastomosis with less inflammatory reaction, granulomatous proliferation, and collagen deposition after magnetic compression anastomosis than that after handsewn. [26][27][28] Perhaps not surprisingly, magnetic anastomosis avoids intima injury by needles, and subsequent inflammation caused by suture thread at anastomoses.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Actually, this patient had a primary pancreatic head carcinoma and a swelling and brittle pancreatic body, which might be one of the major reasons for postoperative pancreatic fistula. 40 Although the anastomotic tissue sample was not available in the current study, our previous animal studies have demonstrated that there was always a smoother anastomosis with less inflammatory reaction, granulomatous proliferation, and collagen deposition after magnetic compression anastomosis than that after handsewn. [26][27][28] Perhaps not surprisingly, magnetic anastomosis avoids intima injury by needles, and subsequent inflammation caused by suture thread at anastomoses.…”
Section: Discussionmentioning
confidence: 79%
“…After the surgery, none of the patients had bile leakage, but only one patient developed pancreatic fistula. Actually, this patient had a primary pancreatic head carcinoma and a swelling and brittle pancreatic body, which might be one of the major reasons for postoperative pancreatic fistula …”
Section: Discussionmentioning
confidence: 99%
“…20,23 Given the lack of consensus in the literature, and the potential for severe morbidity from an uncontrolled pancreatic leak, operative drains are placed in the majority of pancreatectomy cases. 7 Considering that operative drains remain heavily utilized, recent literature has focused on selecting patients for drain omission or identifying patients in whom drains can be safely removed early. 20,24,25 Several risk scores are available to stratify patients according to risk of CR-POPF, and many surgeons use these scores to select patients for drain omission.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Reasons commonly given for routine pancreatic drainage are early diagnosis of and management of pancreatic stula, which is a potentially devastating complication. 7 Whether operative drains help prevent or manage complications remains debated. While some clinical trials addressing this question showed similar complications and mortality regardless of closed-suction drain usage, others were stopped early after showing increased mortality in patients without drains.…”
Section: Introductionmentioning
confidence: 99%
“…There are randomized prospective studies that confirm the negative effect of the systematic use of abdominal drainage in distal pancreatectomies and that when they are left in place they should be removed in the first 3 days of the postoperative period . The authors highlight the importance of respecting a safety margin of 10 mm around the portal vein in the transection of the parenchyma to avoid any injury to this vein.…”
mentioning
confidence: 97%